A Synthetic Hybrid Molecule for the Selective Removal of Human Pluripotent Stem Cells from Cell Mixtures. Issue 7 (9th January 2017) - Mao, Di; Ando, Shin; Sato, Shin‐ichi; Qin, Ying; Hirata, Nao; Katsuda, Yousuke; Kawase, Eihachiro; Kuo, Ting‐Fang; Minami, Itsunari; Shiba, Yuji; Ueda, Kazumitsu; Nakatsuji, Norio; et al.
Abstract: A major hurdle in stem cell therapy is the tumorigenic risk of residual undifferentiated stem cells. This report describes the design and evaluation of synthetic hybrid molecules that efficiently reduce the number of human induced pluripotent stem cells (hiPSCs) in cell mixtures. The design takes advantage of Kyoto probe 1 (KP‐1), a fluorescent chemical probe for hiPSCs, and clinically used anticancer drugs. Among the KP‐1–drug conjugates we synthesized, we found an exceptionally selective, chemically tractable molecule that induced the death of hiPSCs. Mechanistic analysis suggested that the high selectivity originates from the synergistic combination of transporter‐mediated efflux and the cytotoxicity mode of action. The present study offers a chemical and mechanistic rationale for designing selective, safe, and simple reagents for the preparation of non‐tumorigenic clinical samples. Abstract : Wiping out stem cells : A major obstacle in stem cell therapy is the tumorigenic risk of residual undifferentiated stem cells. Fluorescent hybrid molecules were synthesized for the selective removal of human induced pluripotent stem cells from cell mixtures. The high selectivity results from the synergy between the transporter‐mediated efflux and the cytotoxicity mode of action.